Comparison of Anticancer Properties of Annona muricata L. Acetonic and Methanolic Leaf Extracts - de Castro Nascimento, Jéssica; do Vale Bosso, Rosa M.; Anholeti, Maria Carolina; da Silva Castro, Elaine; Junior, Maximino A. B.; do Nascimento, Thais Affonso; de Paiva, Selma Ribeiro; Fonte de Amorim, Lidia Maria da (Natural Products Journal, The, 2019)
Background: Phytochemical studies of Annona muricata showed the presence of bioactive components with anticancer activity. We compared the anticancer properties of crude acetonic and methanolic A. muricata leaf extracts. Methods: The viabilities of different cell lines (A549, U87, U251, K562 and VERO) treated with A. muricata acetonic or methanolic leaf extracts were measured using the MTT assay. Apoptosis induction, cell cycle and cytoskeleton rearrangements were evaluated in K562 by flow cytometry or fluorescence microscopy. Results: Chemical analyses of the A. muricata extracts showed differences in their composition. The K562 cell line was the most sensitive to the treatment with the acetonic and methanolic extracts, and the IC50 values, respectively were 28.82 (24.41 - 34.69) and 32.49 (27.21 - 40.16) μg/mL. Both extracts induced apoptotic cell death and G0/G1 phase cell cycle arrest. For the first time, cytoskeleton rearrangements were observed in the K562 cell line treated with methanolic extract. Conclusion: These findings suggest that both A. muricata extracts exhibit antileukemic potential and represent a promising source of novel compounds with anticancer activity.
Keywords: Graviola